PENDIDIKAN KARAKTER PADA KELUARGA IDAMAN KELURAHAN TERJUN KECAMATAN MEDAN MARELAN - Hidayah sirait, Nurul Hidayah (Universitas Dharmawangsa, 2025)
This study aims to examine and describe the process ofcharacter education in families, particularly in the family environmentin Terjun Village, Medan Marelan District. The main focus of the studyincludes the character values instilled by parents, the methods used toinstill them, and the implications of applying these methods onchildren's character development. The method used in this study is aqualitative approach with data collection techniques throughobservation, in-depth interviews, and documentation studies. Theresults of the study show that character values such as honesty,discipline, responsibility, and empathy have been instilled throughmodeling, habituation, and effective communication. Despiteobstacles such as low parental education levels and limited emotionalrelationships within the family, the implementation of planned andcontinuous character education can improve children's moral andsocial development. This study is expected to contribute to thedevelopment of effective family character education strategies tocreate harmonious families and a strong-charactered youngergeneration.